The Effectiveness of Career Guidance Services Based on Career Adaptability in Improving Students' Job Readiness: An Experimental Study at Vocational School ​ - Pinem, Mety Leontiana; Dahlia Novarianing Asri (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2026)
The low level of work readiness of vocational high school students is due to the lack of ability to adapt to the dynamics of the modern work world. Career guidance services based on career adaptability emphasize four aspects, namely concern, control, curiosity, and confidence. The purpose of this study is to test the effectiveness of career guidance services based on career adaptability in improving the work readiness of vocational high school students. This study uses a quantitative approach with an experimental method with a one-group pretest-posttest design. The sample of this study was 30 students majoring in Motorcycle Engineering. The sampling technique used purposive sampling. The instrument to measure work readiness uses a work readiness scale that includes 4 aspects, namely (1) personal characteristics, (2) organizational intelligence, (3) work competence and (4) social competence. The results of the study indicate that career guidance services based on career adaptability are significantly effective in improving the work readiness of vocational high school students. This is indicated by the value of t = -18.33, p <0.05. Career guidance services based on career adaptability can be a strategic alternative in career guidance services in vocational high schools to produce graduates who are more prepared and adaptive to industry needs.